IMAGING DIAGNOSIS—COMPUTED TOMOGRAPHY FINDINGS IN A CASE OF METASTATIC OVARIAN ADENOCARCINOMA IN A DOG. Issue 6 (13th October 2016) - Rowan, Conor; Cuddy, Laura; Bryan, Jill; Shiel, Robert; Hoey, Séamus
Abstract: A 5‐year‐old female entire German Shepherd presented for otitis and lethargy. An incidental abdominal mass was identified on examination. Ultrasound examination (US) identified a heterogeneous left ovarian mass. Computed tomography (CT) was performed for surgical planning and staging. The reproductive tract was removed en bloc and submitted for histopathology. Multiple small (1–5 mm) nodules identified at coeliotomy on the surface of the liver, spleen and peritoneum were biopsied. The lesions were not visible on CT nor US on review. This is the first case report of the CT findings of ovarian papillary adenocarcinoma with carcinomatosis.